Market Mechanisms as a Social Deadlock for Russian Education - A. M. Osipov (Высшее образование в России)
InRussia, the preference of the educational policy for market paths has been being formed for nearly thirty years. The mechanisms, consequences and prospects of so called marketization have not been yet studied. The article considers the marketization of education, including higher education, as a scientific and social problem. Basing on foreign and domestic sources, the author proves that the marketization of education is generated by neo-liberal attitude of the financial and economic elites seeking to reduce state budget expenditures in the social sphere and keep up the disintegration of society and to secure their future domination. The state, the bureaucratic apparatus of the education system, educators’ and researchers’ communities do not take up the problem of education marketization and its consequences. The marketization strategy along with its derivatives is taken in society as an axiom, without special studies and research. Due to this education is being dysfunctional, it experiences a protracted institutional crisis, social tensions and losses, whilst the search of ways out of the neoliberal deadlock is postponed up to uncertain future.